Kingdom-specific lipid unsaturation calibrates sequence evolution in membrane arm subunits of eukaryotic respiratory complexes - Pooja Gupta; Sristi Chakroborty; Arun K. Rathod; K. Ranjith Kumar; Shreya Bhat; Suparna Ghosh; Pallavi Rao T; Kameshwari Yele; Raman Bakthisaran; R. Nagaraj; Moutusi Manna; Swasti Raychaudhuri (Nature Communications)
Abstract Sequence evolution of protein complexes (PCs) is constrained by protein-protein interactions (PPIs). PPI-interfaces are predominantly conserved and hotspots for disease-related mutations. How do lipid-protein interactions (LPIs) constrain sequence evolution of membrane-PCs? We explore Respiratory Complexes (RCs) as a case study as these allow to compare sequence evolution in subunits exposed to both lipids in inner-mitochondrial membrane (IMM) and lipid-free aqueous matrix. We find that lipid-exposed surfaces of the IMM-subunits but not of the matrix subunits are populated with non-PPI disease-causing mutations signifying LPIs in stabilizing RCs. Further, IMM-subunits including their exposed surfaces show high intra-kingdom sequence conservation but remarkably diverge beyond. Molecular Dynamics simulation suggests contrasting LPIs of structurally superimposable but sequence-wise diverged IMM-exposed helices of Complex I (CI) subunit Ndufa1 from human and Arabidopsis depending on kingdom-specific unsaturation of cardiolipin fatty acyl chains. in cellulo assays consolidate inter-kingdom incompatibility of Ndufa1-helices due to the lipid-exposed amino acids. Plant-specific unsaturated fatty acids in human cells also trigger CI-instability. Taken together, we posit that altered LPIs calibrate sequence evolution at the IMM-arms of eukaryotic RCs.